The Predictive Power of Social Media Use and Body Image on Eating Attitudes in Youth - Okonkwo, Adaeze; Dlamini, Thandiwe (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: The objective of this study was to investigate the predictive power of social media use and body image perceptions on eating attitudes among youth in South Africa.Methods and Materials: A correlational descriptive research design was employed involving 350 South African youth participants selected using stratified random sampling, with sample size determined according to Morgan and Krejcie's table. Data were collected using standardized instruments: Eating Attitudes Test (EAT-26), Social Media Use Integration Scale (SMUIS), and Body Shape Questionnaire (BSQ), all validated in previous research. Data analysis was performed using SPSS-27 software, employing descriptive statistics, Pearson correlation coefficients, and linear regression analyses.Findings: The mean scores for Eating Attitudes (24.53 ± 6.42), Social Media Use (38.29 ± 7.56), and Body Image (107.45 ± 22.18) indicated moderate maladaptive eating behaviors and significant variability in social media usage and body dissatisfaction. Pearson correlation analyses revealed significant positive correlations between Eating Attitudes and Social Media Use (r = .38, p < .01) and Body Image (r = .57, p < .01). Linear regression analyses demonstrated that social media use and body image significantly predicted maladaptive eating attitudes (F(2, 347) = 103.48, p < .01, R² = .37), with body image emerging as the stronger predictor (β = .52, p < .01) compared to social media use (β = .18, p < .01).Conclusion: These results underscore the importance of addressing both social media consumption habits and negative body perceptions through targeted interventions to improve healthy eating attitudes and psychological well-being among youth.